Empirical Analysis Of Core Value Statements Of Financial Institutions In Nigeria: A Strategic Finance Approach - Gbenga Festus Babarinde; Tajudeen Idera Abdulmajeed; Hamzat Kabir Mohammed; Akeem A Opoola (Universitas Kuningan, 2022)
Mission, values, vision and objectives are considered essential in strategic planning and management activities of any organization, in that they function together to determine its strategic direction. The objective of this study is to identify, classify and analyse core value statements of financial institutions quoted on the Nigerian Stock Exchange. Based on simple random sampling and in line with the Godden (2004)’s sample size formula, a sample of 38 was selected out of a population of 52 financial institutions. The selected financial institutions have 209 core value statements, which were classified into seven value dimensions: commitment to customers, commitment to stakeholders, commitment to employees, commitment to diversity, commitment to integrity, entrepreneurship, and corporate social responsibility. Using both content and descriptive analyses, the study found that commitment to integrity (33.97%) and commitment to customers (23.92%) are two most popular out of the seven value dimensions. However, commitment to employees constitutes as low as 1.44% of the value dimensions. It is therefore recommended that financial institutions in Nigeria should increase their commitment to employees and practically institutionalize and integrate their core values in the heart of the employees rather than making it a mere statement in black and white